P273 Investigations of the characteristics and efficacy of anti-TNFα agents for optimising treatment in paediatric patients with new-onset Crohn's disease. (25th January 2019) - Yokoyama, Y; Watanabe, K; Kojima, K; Koshiba, R; Fujimoto, K; Sato, T; Kawai, M; Kamikozuru, K; Takagawa, T; Miyazaki, T; Hida, N; Nakamura, S
Abstract: Background: We investigated the characteristics of paediatric Crohn's disease (CD) patients and the efficacy of anti-TNF-α agents in our hospital specialising in inflammatory bowel diseases to illustrate real-world data. Methods: In this single-centre retrospective case–control study, we investigated 236 CD patients newly diagnosed at our hospital from January 2007 to December 2017. The patients were divided into the paediatric group (≤17 years of age) and the non-paediatric group (>17 years of age). We compared clinical characteristics and investigated the efficacies of anti-TNF-α agents. Clinical remission was defined as a Pediatric Crohn's disease Activity Index (PCDAI) ≤10, while loss of response (LOR) was defined as requiring additional or increasing doses of concomitant therapy. Mucosal healing was defined as no active inflammation at any site based on conventional ileocolonoscopy. Results: The paediatric group accounted for 22.9% of CD patients (54/236) and the observational period was 3.9 ± 2.0 years. The age at diagnosis was 14.8 ± 1.9 years in the paediatric CD patients, and males accounted for 66.7% (36/54). The complications of extraintestinal manifestations were significantly more common in the paediatric group (22/54, 40.7%) than in the non-paediatric group (13/182, 7.1%) ( p < 0.001). The inflammatory type of behaviour was significantly more frequent in the paediatric group than in the non-paediatric group (90.7% vs. 59.9%; p < 0.001). In the paediatric group, 78.8% (42/54) of patients were administered anti-TNFα agents (30 cases given infliximab, 12 cases given adalimumab), and 92.9% (39/42) of them were administered without immunomodulators. The rates of achieving remission induction and mucosal healing within a year were 89.2% (33/37) and 75.0% (18/24), respectively. Among 33 primary responders in the paediatric group, the cumulative LOR rate was 21.2% (7/33) at 1 year, 33.3% (11/33) at 2 years and 39.4% (13/33) at 5 years. Significantly lower haemoglobin (10.4 ± 3.1 g/dl vs. 12.5 ± 1.5 g/dl, p < 0.05), higher C-reactive protein (5.5 ± 5.5 mg/dl vs. 2.4 ± 2.3 mg/dl, p < 0.05) and higher PCDAI (41.3 ± 13.4 vs. 28.2 ± 13.8, p < 0.05) at baseline were observed in the LOR group than in the remission maintenance group. There tended to be more females in the LOR group (53.8% vs. 20.8%, p = 0.07). Conclusions: The inflammatory type of behaviour and the complications of extraintestinal manifestations were frequent in our paediatric CD cohort. Although a higher rate of anti-TNFα agent administration depends on the special support system covering the medical costs for CD patients in Japan, LOR developed. The introduction of anti-TNFα agents as combination therapy with immunomodulators should be considered to avoid LOR in high-risk paediatric CD patients.